2013
DOI: 10.1111/cid.12098
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Placement of Implants into Infected Sites: A Systematic Review

Abstract: The high survival rate obtained in several studies supports the hypothesis that implants may be successfully osseointegrated when placed immediately after extraction of teeth presenting endodontic and periodontal lesions, provided that appropriate clinical procedures are performed before the implant surgical procedure such as meticulous cleaning, socket curettage/debridement, and chlorhexidine 0.12% rinse. However, more randomized controlled clinical trials with a longer follow-up are required to confirm this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
112
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(123 citation statements)
references
References 50 publications
(253 reference statements)
0
112
0
11
Order By: Relevance
“…A remoção da raiz se dá por meio do giro do manípulo, no sentido horário observando a manuten-estética nesses casos, por oferecer manutenção da altura das cristas ósseas e do contorno gengival. (9) A exodontia deve ser realizada da maneira mais atraumática possível, a técnica cirúrgica preconizada não realiza incisões ou descolamentos mucoperiosteais, mantendo a vascularização do osso vestibular, minimizando sua reabsorção e preservando as papilas interdentais. Neste caso, foi utilizado o Extrator Dentário (Neodent, Curitiba-Brasil).…”
Section: Relato De Casounclassified
“…A remoção da raiz se dá por meio do giro do manípulo, no sentido horário observando a manuten-estética nesses casos, por oferecer manutenção da altura das cristas ósseas e do contorno gengival. (9) A exodontia deve ser realizada da maneira mais atraumática possível, a técnica cirúrgica preconizada não realiza incisões ou descolamentos mucoperiosteais, mantendo a vascularização do osso vestibular, minimizando sua reabsorção e preservando as papilas interdentais. Neste caso, foi utilizado o Extrator Dentário (Neodent, Curitiba-Brasil).…”
Section: Relato De Casounclassified
“…1 However, alveolar ridge resorption after tooth extraction may considerably reduce the residual bone volume and affect the favorable positioning of implants, which is required for optimal restoration. 2,3 The idea has been proposed of placing the implant immediately into fresh extraction sockets in order to overcome such disadvantages. 4,5 On the other hand, some studies suggest that the bone dimensions of immediate implant sites demonstrated a reduction in vertical and horizontal aspects following surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Immediate loading is defined as 'functional loading of an implant within one week of its placement. 4 This loading protocol of implants in edentulous and partially dentate arches has shown equally successful outcomes as those loaded after a delay of 2-3 months.…”
Section: Introductionmentioning
confidence: 99%